Culturally Responsive Teaching Approach in Learning Mathematics in Primary Schools under the Merdeka Curriculum - Sari, Syafni Gustina; Nora, Yulfia; Afrioza, Lasri; Yeni, Nelda Anda; Zamardi, Randi Ali (Universitas Negeri Padang, 2025)
Mathematics learning in elementary schools is often perceived as abstract and difficult, resulting in low motivation, weak conceptual understanding, and limited confidence among students. This phenomenon poses a challenge in the implementation of the Merdeka Curriculum, which emphasizes differentiated, student-centered, and culturally relevant learning. To address this issue, Culturally Responsive Teaching (CRT) has been introduced as a pedagogical approach that integrates students’ cultural backgrounds into mathematics learning. This study employed a meta-analysis method by reviewing 10 national journal articles published within the last five years. Data were collected through documentation using Google Scholar with the keywords “Culturally Responsive Teaching in mathematics learning.” The analysis was conducted using Wilson and Kelley’s nine-step procedure, focusing on research purposes, design, data collection techniques, and data analysis methods. The results showed that 80% of studies aimed at improving learning outcomes, while 70% applied classroom action research designs. Most data were collected through tests and observations (50%), and analysis predominantly used combined quantitative and qualitative descriptive methods (50%). Overall, the findings indicate that CRT positively impacts students’ mathematical understanding, motivation, creativity, and problem-solving skills. Despite challenges in connecting abstract concepts with cultural contexts, CRT proves effective in creating inclusive, meaningful, and culturally relevant mathematics learning under the Merdeka Curriculum.